Efektifitas Terapi Relaksasi Benson Terhadap Tekanan Darah Pada Penderita Hipertensi - Joko Tri Atmojo; Made Mahaguna Putra; Ni Made Dewi Yunica Astriani; Putu Indah Sintya Dewi; Tjahja Bintoro (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Hypertension is associated with an increase in systolic pressure or diastolic pressure or the pressure of both. Hypertension is defined as persistently high blood pressure where the systolic pressure above 140 mmHg and diastolic pressure above 90 mmHg. One of the non-pharmacological treatments for hypertension is with Benson relaxation therapy. The purpose of this research was to analyze the effect of Benson relaxation therapy on blood pressure in patients with hypertension in Unggahan Village. Method: The research design was a pra-experimental design with one group pre-post test design. The research sample consisted of 30 people. The sampling technique used non-probability sampling with techniques purposive sampling and data from respondents was collected by using a digital tensimeter measuring instrument. This study used a Paired t-test examination significant standard α=0.05. Result: The result of the study shows that before was given a Benson relaxation therapy that was Mean systolic blood pressure is 149.93, and the Mean diastolic blood pressure is 89.33. Then, after giving a Benson relaxation therapy that was Mean systolic blood pressure is 138.97 and the Mean diastolic blood pressure is 84.07. The results of the examination Paired t-test, obtained the score p pre and post (0,000) < α (0,05), which means that H0 is ferected and Ha accepted. Conclusion: Thus, it can be concluded that there is an effect of Benson relaxation therapy on blood pressure in patients with hypertension in Unggahan Village.